A study on morphogenesis of roots of Panax stipuleanatus H.T.Tsai et K.M.Feng in vitro and preliminary determination of oleanolic acid in roots - Hương, Nguyễn Thị Ngọc; Hùng, Trần; Đẹp, Trương Thị (Vietnam Journal of Biotechnology, 2016)
Panax stipuleanatus H.T.Tsai et K.M.Feng which belongs to the genus Panax (Araliaceae family) is an valuable medicinal herbs in Vietnam and China. In the rhizome of Panax stipuleanatus H.T.Tsai et K.M.Feng contains many olean-type triterpenoid saponins, which can improve mental stamina and reduces risks of cancers in humans. Up to now, there is no research on the morphological changes in adventitious root formation from the rhizome of this species. In this study, the callus morphogenesis from the rhizome and the adventitious root morphogenesis from callus were analyzed. The rhizome segments 1-1.5 cm in diameter and 1 cm thick were cultured on MS medium supplemented 30 g/l sucrose, 6 g/l agar and 0.5 mg/l 2.4-D in dark. Callus formed on the surface of the rhizome after four weeks. The first cell divisions occurred in the first two weeks, in secondary cortex parenchyma cells and vascular cambium of the rhizome. 26-week-old callus with slow cell proliferation within the cluster and the long cells outside clusters were transferred to the induced medium supplemented with 0.5 mg/l 2.4-D and 0.1 mg/l TDZ within 6 weeks. The calli were more tight and formed many clusters. The adventitious roots formed 10 weeks after the transfer to MS medium supplemented with 0.5 mg/l NAA. Callus formed spherical structures called embryo-liked but only developed the root pole. Results of the thin layer chromatography using chloroform–methanol (9:1, v/v) showed the presence of oleanolic acid in extracts of adventitious roots fromed from callus-derived rhizomes of Panax stipuleanatus H.T.Tsai et K.M.Feng.